2019
DOI: 10.5152/tud.2014.66674
|View full text |Cite
|
Sign up to set email alerts
|

Does body mass index effect the success of percutaneous nephrolithotomy?

Abstract: Objective: In obese patients, the management of renal calculi presents a number of challenges for urologists. In this study, we aimed to evaluate the efficacy and safety of percutaneous nephrolithotomy (PNL) proce dure in obese and morbidly obese patients. Material and methods:We retrospectively reviewed the medical files of 2360 patients treated with PNL between March 2002 and April 2013. The patients were stratified into four groups according to the World Health Organization (WHO) classification of body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Additionally, body mass index does not affect success rates or the frequency of complications post-PCNLl. 21 In present study, ileus (without need NG tube), fever and transient hematuria were almost similarly encountered among the three groups (Clavien grade 1 complications). Interestingly, transfusion rates were not dissimilar among these groups (see Table-III ) and statistically the difference was insignificant (p=0.73).…”
Section: Discussionsupporting
confidence: 66%
“…Additionally, body mass index does not affect success rates or the frequency of complications post-PCNLl. 21 In present study, ileus (without need NG tube), fever and transient hematuria were almost similarly encountered among the three groups (Clavien grade 1 complications). Interestingly, transfusion rates were not dissimilar among these groups (see Table-III ) and statistically the difference was insignificant (p=0.73).…”
Section: Discussionsupporting
confidence: 66%
“…In a study done by Şimşek et al, patients who underwent PNL in the prone position were divided into 4 groups according to BMI: normal body weight (BMI <25 kg/m2), overweight (BMI 25-29.9 kg/m2), obese (BMI 30-39 kg/m2) and morbidly obese (BMI >40 kg/m2). It was reported that there was no significant difference related to the complication rates between all groups (10). Additionally, in the study conducted by Ferreira et al, it was indicated for obese and non-obese patients who had PNL performed that no considerable difference was identified in terms of overall complication rates (13.8% and 13.6%, respectively, as Clavien grade ≥1) and major complication rates (8.4% and 5%, respectively as Clavien grade ≥3) (13).…”
Section: Discussionmentioning
confidence: 90%
“…Studies demonstrate that concerning treating nephrolithiasis in obese patients, both prone PNL and supine PNL are safe techniques with high effectiveness and emphasize that the complication rates for individuals with obesity are similar to those of the general population (10,13). In a study done by Şimşek et al, patients who underwent PNL in the prone position were divided into 4 groups according to BMI: normal body weight (BMI <25 kg/m2), overweight (BMI 25-29.9 kg/m2), obese (BMI 30-39 kg/m2) and morbidly obese (BMI >40 kg/m2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations